2022
DOI: 10.3389/fonc.2022.928373
|View full text |Cite
|
Sign up to set email alerts
|

FBP1 /miR-24-1/enhancer axis activation blocks renal cell carcinoma progression via Warburg effect

Abstract: Warburg effect is a pivotal hallmark of cancers and appears prevalently in renal cell carcinoma (RCC). FBP1 plays a negative role in Warburg effect as a rate-limiting enzyme in gluconeogenesis, yet its mechanism in RCC remains to be further characterized. Herein, we revealed that FBP1 was downregulated in RCC tissue samples and was related to the poor survival rate of RCC. Strikingly, miR-24-1 whose DNA locus is overlapped with enhancer region chr9:95084940-95087024 was closely linked with the depletion of FBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…1 D); detailed descriptions are listed in Table S4 . In the top 5 down-regulated genes, the regulatory functions of ALDOB [ 37 , 38 ], GPX3 [ 39 ] and FBP1 [ [40] , [41] , [42] ] in RCC have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…1 D); detailed descriptions are listed in Table S4 . In the top 5 down-regulated genes, the regulatory functions of ALDOB [ 37 , 38 ], GPX3 [ 39 ] and FBP1 [ [40] , [41] , [42] ] in RCC have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nuclear-activating RNA (NamiRNA) localizes itself in the nucleus and activates proximal or distal genes by targeting enhancers [29]. Dongen Ju et al found that miR-24-1 inhibited the Warburg effect in cancer cells by targeting the active enhancer in the nucleus to activate FBP1 transcription and slow down aerobic glycolysis, ultimately preventing the development of renal cell carcinoma [30]. Younger et al designed miRNA mimics that specifically bind to target gene promoters and directly inhibit gene transcription [31].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (32) investigated the mechanisms underlying the role of miR-1236-3p in RCC progression and found that miR-1236-3p directly targets the P21 promoter to regulate its gene expression by using a ChIP assay with biotinylated miR-1236-3p, with the ultimate effect to inhibit its function and leading to the suppression of RCC cell proliferation. The result of a luciferase reporter assay showed that miR-24-1 overexpression enhanced fructose-1,6-bisphosphatase transcription by increasing its enhancer activity to attenuate RCC proliferation and metastasis (33).…”
Section: Mirnas In Urinary System Cancersmentioning
confidence: 99%